Investigation of Novel RNA Elements in the 3′UTR of Tobacco Necrosis Virus-D - Laura R. Newburn; Baodong Wu; K. Andrew White (Viruses, 2020)
RNA elements in the untranslated regions of plus-strand RNA viruses can control a variety of viral processes including translation, replication, packaging, and subgenomic mRNA production. The 3′ untranslated region (3′UTR) of Tobacco necrosis virus strain D (TNV-D; genus Betanecrovirus, family Tombusviridae) contains several well studied regulatory RNA elements. Here, we explore a previously unexamined region of the viral 3′UTR, the sequence located upstream of the 3′-cap independent translation enhancer (3′CITE). Our results indicate that (i) a long-range RNA–RNA interaction between an internal RNA element and the 3′UTR facilitates translational readthrough, and may also promote viral RNA synthesis; (ii) a conserved RNA hairpin, SLX, is required for efficient genome accumulation; and (iii) an adenine-rich region upstream of the 3′CITE is dispensable, but can modulate genome accumulation. These findings identified novel regulatory RNA elements in the 3′UTR of the TNV-D genome that are important for virus survival.